2022
DOI: 10.1096/fj.202101656rr
|View full text |Cite
|
Sign up to set email alerts
|

CatSper and its CaM‐like Ca 2+ sensor EFCAB9 are necessary for the path chirality of sperm

Abstract: Successful fertilization depends on sperm motility adaptation. Ejaculated and activated sperm beat symmetrically in high frequency, move linearly, and swim with clockwise chirality. After capacitation, sperm beat asymmetrically with lower amplitude and a high lateral head excursion. This motility change called hyperactivation requires CatSper activation and an increase in intracellular Ca2+. However, whether CatSper‐mediated Ca2+ influx participates in controlling the swim path chirality is unknown. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 95 publications
(303 reference statements)
0
11
0
Order By: Relevance
“…This is likely caused by the lack of xy -displacement response during capacitation, and highlights the importance of the intact higher-order assembly of CatSper complex for orchestrating CatSper channel activity and thus effective sperm navigation during capacitation. In addition, we have previously shown that wild type sperm exhibit a strict clockwise swimming path 33 , whereas this chirality is randomized in Efcab9 −/− sperm 37 . Based on our structural findings and the motility defects in Efcab9 −/− sperm, we propose that in wild type sperm the connected higher-order zigzag arrangement within a longitudinal nanodomain could allow for coordinated opening of the entire array of CatSper channels along the flagellar axis, ensuring a large and synchronized Ca 2+ influx to generate strong bending force (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 93%
“…This is likely caused by the lack of xy -displacement response during capacitation, and highlights the importance of the intact higher-order assembly of CatSper complex for orchestrating CatSper channel activity and thus effective sperm navigation during capacitation. In addition, we have previously shown that wild type sperm exhibit a strict clockwise swimming path 33 , whereas this chirality is randomized in Efcab9 −/− sperm 37 . Based on our structural findings and the motility defects in Efcab9 −/− sperm, we propose that in wild type sperm the connected higher-order zigzag arrangement within a longitudinal nanodomain could allow for coordinated opening of the entire array of CatSper channels along the flagellar axis, ensuring a large and synchronized Ca 2+ influx to generate strong bending force (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 93%
“…The 4D movement analysis in the current study confirms these abnormalities in motility and extend them by identifying a decrease in the flagellar excursion in the Z-plane. In our recent work, we show a possible connection between the intracellular Ca 2+ concentration and the swimming path chirality, by demonstrating that an alteration of the Ca 2+ homeostasis after contact to ZP2 or by mutation of the CATSPER channel, the main Ca 2+ channel in sperm flagellum [15,18,21], lead to a substantial change in path chirality [43]. CABYR is a calcium-binding protein localized in the principal piece, is phosphorylated during sperm capacitation and may play a role for capacitation-dependent phosphorylation in calcium signaling [45,67].…”
Section: Cabyr Maintains Conserved Path Chiralitymentioning
confidence: 89%
“…In earlier studies, we showed that non-capacitated as well as capacitated murine sperm have a conserved CW path chirality and proposed, that this swimming pattern is necessary for reaching the oocyte [21,39,43]. We further postulate that substantial changes in the intracellular Ca 2+ concentration result in a loss of chirality and speculate that this is an important requirement to finalize fertilization [43]. In this study, we find that also a change in intracellular cAMP and ADP concentrations leads to a loss of path chirality in non-capacitated mouse sperm.…”
Section: Camp Plays a Central Role In Regulating Flagellar Movementmentioning
confidence: 99%
See 2 more Smart Citations